Early Childhood Teachers Finding Voice among Peers: A Reflection on Practice. Issue 1 (2nd January 2019) - Recchia, Susan L.; Puig, Victoria I.
ABSTRACT: This reflective narrative explores the voices of two participants in the Early Childhood Professional Mentoring Group (ECPMG), created in response to our graduates' concerns about their lack of support as they entered the field of inclusive early childhood education. Building on their existing relationships with each other, and with us as their former instructors, the group fostered a community in which our graduates could engage in reciprocal peer support and group problem solving, developing their skills as educators, professionals, and reflective change agents. This model contrasts with other forms of professional development that follow a set agenda facilitated by an assigned leader. The open structure and lack of hierarchy in the group invited spontaneous discussions of daily practices and challenges, and allowed different styles of expression to emerge. Our reflective narrative on our work with the ECPMG highlights the power of peers in providing induction and mentoring support, and the value to teacher educators of listening to multiple voices in hearing new teachers' stories. We suggest that this type of mentoring be considered as an essential element of early childhood teacher education.